Molecular characterization of KU70 and KU80 homologues and exploitation of a KU70-deficient mutant for improving gene deletion frequency in Rhodosporidium toruloides - Koh, Chong Mei John (BioMed Central, 2014)
BACKGROUND: Rhodosporidium toruloides is a β-carotenoid accumulating, oleaginous yeast that has great biotechnological potential. The lack of reliable and efficient genetic manipulation tools have been a major hurdle blocking its adoption as a biotechnology platform. RESULTS: We report for the first time the development of a highly efficient targeted gene deletion method in R. toruloides ATCC 10657 via Agrobacterium tumefaciens-mediated transformation. To further improve targeting frequency, the KU70 and KU80 homologs in R. toruloides were isolated and characterized in detail. A KU70-deficient mutant (∆ku70e) generated with the hygromycin selection cassette removed by the Cre-loxP recombination system showed a dramatically improved targeted gene deletion frequency, with over 90% of the transformants being true knockouts when homology sequence length of at least 1 kb was used. Successful gene targeting could be made with homologous flanking sequences as short as 100 bp in the ∆ku70e strain. KU70 deficiency did not perturb cell growth although an elevated sensitivity to DNA mutagenic agents was observed. Compared to the other well-known oleaginous yeast, Yarrowia lipolytica, R. toruloides KU70/KU80 genes contain much higher density of introns and are the most GC-rich KU70/KU80 genes reported. CONCLUSIONS: The KU70-deficient mutant generated herein was effective in improving gene deletion frequency and allowed shorter homology sequences to be used for gene targeting. It retained the key oleaginous and fast growing features of R. toruloides. The strain should facilitate both fundamental and applied studies in this important yeast, with the approaches taken here likely to be applicable in other species in subphylum Pucciniomycotina.